Hubungan Kompetensi Kepribadian Guru PAK dan Budi Pekerti dengan Tingkah Laku Peserta Didik Kelas V SD Negeri 173551 Laguboti Tahun Pembelajaran 2023/2024 - Cristi Giovanni Sitompul; Boho Parulian Pardede; Goklas J Manalu; Hasudungan Simatupang; Maryska Debora Silalahi (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The purpose of this study is to determine the positive and significant relationship between the PAK Teacher Personality Competition and Ethics and Student Behavior in grade V of SDN 173551 Laguboti for the 2023/2024 Academic Year. The method used in this study is a quantitative method with a descriptive approach. The population is the entire class V students of SD Negeri 173551 Laguboti which totals 54 people and this study is a population study. Data was collected with a positive closed questionnaire of 39 items, namely 19 items for variable X and 20 items for variable Y. The results of data analysis showed that there was a positive and significant relationship between teacher personality competence and the behavior of grade V students of SD Negeri 173551 Laguboti for the 2023/2024 academic year, as evidenced by the following data analysis: 1) A positive relationship test obtained a value of rxy = 0,559 > rtabel(a=0,05,n=54) = 0,226 thus it is known that there is a positive relationship between variable X and variable Y. 2) A significant relationship test obtained a value of tcal thitung= 4,856 > ttabel(a=0,05,dk=n-2=52)=2,000 thus there is a significant relationship between variable X and variable Y. Thus Ha is accepted and H0¬ which says there is no relationship is rejected.